Salience and Blindness: A Haptic Hike on Gins Mountain - Marie-Dominique Garnier (Revue de Géographie Alpine)
This paper attempts to follow an improbable ridge line between architecture, geography and linguistics, between the optic and haptic ends of the concept of salience, through a reading of Helen Keller Or Arakawa, Madeline Gins’s 1994 essay-cum-joint-biography partly devoted to “salience” approached through the blind figure of Helen Keller (1880-1968). In a chapter titled “Or Mountains Or Lines”, prominent features envisaged from a sighted perception give way, under the condition of blindness, to saddle-points, swivel-areas and moments of stylistic tentativeness when words and/or syntax begins to fail. Salience, revisited through Keller’s apprehension of mountains as vaporous and mobile masses, leads to tentativeness in writing and to what I here call “failience” in discourse: the failure to stabilise discursive referents, the unsettling reversibility of syntactic lines based, for example, on the swivel-point of an “-ing” form. At work in Gins’s writing is the invention of a cathectic, tactile grasp of the world through langage. In order to ease access to a “faulty” perception, Gins invites her readers to transit through the writing of blind cartographer William Prescott, in particular through his “tactile”, linear mapping of the Andes Cordillera, approached as a mobile rhizome rather than as a collection of fixed, “raised” points. Mapping, under conditions of blindness, implies wander lines as much as lines of (thin) air.